(3eLdj GdMRf Yf GdeMRhf aj efGbH GdTjN Ydi Hf ejehfs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LGO YdjfG HNOeI GdCTQGa s
(3UGMH gPg GdefGbH gh GdEeGe GdYGQa HGddg Ydi Hf ejehf GdeZQHis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B333 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B230 s
Keywords: (3GdJGQjNs